Pengaruh Sistem Akuntansi Manajemen Terhadap Kinerja Manajerial Dengan Strategi Bisnis Sebagai Variabel Pemoderasi - Rizki Fitri Amalia (Politeknik Ganesha Medan, 2022)
This study aims to determine the effect of the management accounting system on managerial performance with business strategy as a moderating variable. The type of research in this study is causal associative. The population in this study is a hotel in the city of Palembang. The sample selected is 3 to 5 star hotels. The sample technique used in this study is purposive sampling and the samples used in this study were 63 samples. Hypothesis testing was carried out using the moderation regression analysis method with the help of SPSS ver 26. The results obtained showed that business strategy was not able to strengthen the relationship between management accounting systems and managerial performance.